Increased complications of COVID-19 in people with cardiovascular disease: Role of the renin–angiotensin-aldosterone system (RAAS) dysregulation. (5th January 2022) - Augustine, Robin; S, Abhilash; Nayeem, Ajisha; Salam, Shaheen Abdul; Augustine, Priya; Dan, Pan; Maureira, Pablo; Mraiche, Fatima; Gentile, Carmine; Hansbro, Philip M.; McClements, Lana; Hasan, Anwarul
Abstract: The rapid spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID‐19), has had a dramatic negative impact on public health and economies worldwide. Recent studies on COVID-19 complications and mortality rates suggest that there is a higher prevalence in cardiovascular diseases (CVD) patients. Past investigations on the associations between pre-existing CVDs and susceptibility to coronavirus infections including SARS‐CoV and the Middle East Respiratory Syndrome coronavirus (MERS-CoV), have demonstrated similar results. However, the underlying mechanisms are poorly understood. This has impeded adequate risk stratification and treatment strategies for CVD patients with SARS-CoV-2 infections. Generally, dysregulation of the expression of angiotensin‐converting enzyme (ACE) and the counter regulator, angiotensin‐converting enzyme 2 (ACE2) is a hallmark of cardiovascular risk and CVD. ACE2 is the main host receptor for SARS-CoV-2. Although further studies are required, dysfunction of ACE2 after virus binding and dysregulation of the renin-angiotensin-aldosterone system (RAAS) signaling may worsen the outcomes of people affected by COVID-19 and with preexisting CVD. Here, we review the current knowledge and outline the gaps related to the relationship between CVD and COVID-19 with a focus on the RAAS. Improved understanding of the mechanisms regulating viral entry and the role of RAAS may direct future research with the potential to improve the prevention and management of COVID-19. Graphical abstract: Image 1 Highlights: There is a higher risk of COVID-19 amongst people with cardiovascular disease. Dysregulation of ACE and the counter regulator, ACE2, is a hallmark of CVD. SARS-CoV-2 binding results in ACE2 dysfunction and dysregulation of the RAAS. High level of Angiotensin II results in pathological events in COVID-19 patients.